Eksplorasi Proses Kreatif Garis dalam Art Therapy untuk Menjaga Kesehatan Mental Siswa MAN 1 Kota Semarang - Tia Hafida Sasanti; Bangkit Sanjaya (LPPM Institut Pendidikan Nusantara Global, 2026)
Student mental health is an important aspect in the educational process, but the utilization of fine arts learning as a medium to support psychological well-being is still not optimal. This study aims to explore the creative process of line drawing in an art therapy approach as an effort to maintain the mental health of students at MAN 1 Semarang City. This study uses a qualitative approach with a descriptive phenomenological method. Data collection through observation of the creative process, in-depth interviews with students, and visual analysis of the line works. The analytical framework refers to Carol D. Ryff's theory of psychological well-being, specifically the dimensions of self-acceptance, environmental mastery, and emotional regulation. The results show that the line characters produced by students such as vibrating, broken, repetitive curves, and short patterned lines represent the emotional state and subjective experiences of students during the drawing process. The creative process of line drawing functions as a medium for nonverbal expression, emotional regulation, and creating a sense of safety and comfort in art learning. These findings confirm that focusing on the creative process, not just the final work, allows for a deeper understanding of students' mental health conditions. This study contributes to the development of art therapy-based art learning practices in schools as a preventive and humanistic approach to supporting students' psychological well-being.